Exposure to a natural nitric oxide donor negatively affects the potential influx of rubidium in potassium-starved Arabidopsis plants - Oliferuk, Sonia (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.